IDENTIFIKASI ALAT PENANGKAPAN IKAN RAMAH LINGKUNGAN BERBASIS CCRF DI KABUPATEN PIDIE, ACEH - Makwiyah A. Chaliluddin; Muhammad Ikram; Djamani Rianjuanda (JURNAL GALUNG TROPIKA, 2019)
Pidie district is one of the producers of capture fisheries in Aceh Province with a number of fishermen reaching 1,019. Sea fishing activities are open access causing concern to the stock of fish resources in the waters. Many fishing operations that use fishing gear that are not environmentally friendly if not managed properly will cause fish resources to decline or overfishing. This study aims to identified environmentally friendly fishing tools based on the Code of Conduct for Responsible Fisheries (CCRF) in Pidie District. This research was conducted in March 2019 in the waters of Pidie District. Data collection was done by interview and direct observation in the field. Analysis of the environmental friendliness of fishing gear based on weighting the score with the Analysis Hiercy Process (AHP) method. The results showed that the fishing gear included in the category of very environmentally friendly, namely; handline, longline, gillnet, and purse seine. While the fishing gear category is not environmentally friendly, namely; Modified beach seine and beach seine.